How good is the Myers-Briggs Type Indicator for predicting leadership-related behaviors? - Zárate-Torres, Rodrigo; Correa, Juan C. (Frontiers in Psychology, 2023)
The Myers-Briggs Type Indicator (MBTI) is a popular tool used by psychologists working as managers' coaches in organizational contexts. Despite its popularity, few studies provide empirical evidence on the role of the MBTI as a predictor of managers' leadership-related behaviors. blueThis article is written based on research that answers the question of how good the MBTI is to prove leadership behavior. It does so by comparing goodness-of-fit indexes of two confirmatory factor analysis models and two structural models on the personality-leadership relationship, following standards of reproducible research principles. We sampled 529 participants who were graduate and undergraduate students enrolled in business administration programs from Colombian universities. Results show conclusive evidence of the psychometric measurement of both MBTI and leadership practices, even though the relationship between MBTI and the leadership practices inventory proved to be weak.